FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BERMASALAH (Studi Kasus di BMT Artha Barokah Yogyakarta 2013) - Widya Astuti; Teguh Suripto (JESI (Jurnal Ekonomi Syariah Indonesia), 2015)
Abstract Widya Astutik. 2010. “Factors Affecting Financing Problem In Barokah BMT Artha Yogyakarta in 2013”. Essay. Yogyakarta: School of Theology Alma Ata. KJKS BMT is an institution that serves as an intermediary (Intermediary Institution) ﬁ nancial, KJKS BMT third parties to channel the funds to the community. Among them is the ﬁ nancing of proﬁ t and loss sharing. The background of this study is that the factor of the customer, the bank and is a factor taken into consideration by the Bank to analyze the occurrence of ﬁ nancing problems at BMT Artha Barokah. This study was conducted to determine whether the factor of the customer, the Bank, and inﬂ uence the occurrence of ﬁ nancing problems. This research is a ﬁ eld research (ﬁ eld reserch) with the data collection methods of documentation, because the data used in this research is secondary data obtained from customer data instantly ﬁ lled. The analysis tool used is multiple linear regression testing using aberration test classical linear regression and statistical tests. The results of t test analysis showed that each of the independent variables signiﬁ cantly affect the ﬁ nancing problems in BMT Artha Barokah Yogyakarta. In the F test showed that the independent variables and external customers signiﬁ cant effect, while the factors did not signiﬁ cantly affect bank ﬁ nancing problems. The determinansi coefﬁ cient (R ²) of 0.56, which means ﬁ nancing bermasalahpada BMT Artha Barokah able to be explained by the independent variable of 56.1% and the remaining 43.9% is inﬂ uenced by other variables outside this research model. Keywords: Affe cting ﬁ nancing problem